Effects of facial nerve axotomy on Th2- and Th1-associated chemokine expression in the facial motor nucleus of wild-type and pre-symptomatic mSOD1 mice - Wainwright, Derek A. (2009)
We have previously demonstrated a neuroprotective mechanism of facial motoneuron (FMN) survival after facial nerve axotomy that is dependent on CD4(+) Th2 cell interaction with peripheral antigen-presenting cells, as well as CNS resident microglia. To investigate this mechanism, we chose to study the Th2-associated chemokine, CCL11, and Th1-associated chemokine, CXCL11, in wild type and presymptomatic mSOD1 mice after facial nerve axotomy. In this report, the results indicate that CCL11 is constitutively expressed in the uninjured facial motor nucleus, but CXCL11 is not expressed at all. Facial nerve axotomy induced a shift in CCL11 expression from FMN to astrocytes, whereas CXCL11 was induced in FMN. Differences in the number of CCL11- and CXCL11-expressing cells were observed between WT and mSOD1 mice after facial nerve axotomy.